Custom, culture and crime: A restorative justice response to culturally motivated crimes in South Africa - Matthee, Jacques (SA crime quarterly, 2025)
South Africa’s 1996 Constitution introduced a dual legal system, recognising African customary law and common law traditions. This article examines how culturally motivated crimes challenge South Africa’s retributive criminal justice system, and explores restorative justice as a more appropriate alternative. Using doctrinal research methods, it analyses constitutional provisions, case law, statutory developments and indigenous practices to evaluate how cultural rights can be integrated into criminal law without undermining justice. The findings show that while South African courts have historically marginalised customary law in criminal proceedings, the Constitution provides a framework for greater incorporation of indigenous principles, particularly restorative, participatory processes that emphasise healing and accountability. The article shows that customary justice practices inherently reflect the fundamental principles of restorative justice. Accordingly, it recommends leveraging existing mechanisms such as victim-offender mediation, family group conferencing and restorative circles as culturally responsive alternatives for addressing culturally motivated crimes in South Africa.